2010
DOI: 10.1088/1367-2630/12/6/065015
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electric field sensitivity of rf-dressed Rydberg dark states

Abstract: Optical detection of Rydberg states using electromagnetically induced transparency (EIT) enables continuous measurement of electric fields in a confined geometry. In this paper, we demonstrate the formation of rf-dressed EIT resonances in a thermal Rb vapour and show that such states exhibit enhanced sensitivity to dc electric fields compared to their bare counterparts. Fitting the corresponding EIT profile enables precise measurements of the dc field independent of laser frequency fluctuations. Our results in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 25 publications
3
65
0
2
Order By: Relevance
“…[12]). Bason et al [13] used nonresonant dressing fields to increase the sensitivity of Rydberg state energies to dc electric fields, and Sevinçli and Pohl [14] have explored the influence of multiple dressing fields on Rydberg-Rydberg interactions. Recently, Jones et al [15] experimentally demonstrated a significant reduction in the electric field dependence of low-ℓ Rydberg-Rydberg transition frequencies through the application of a non-resonant dressing field.…”
Section: Introductionmentioning
confidence: 99%
“…[12]). Bason et al [13] used nonresonant dressing fields to increase the sensitivity of Rydberg state energies to dc electric fields, and Sevinçli and Pohl [14] have explored the influence of multiple dressing fields on Rydberg-Rydberg interactions. Recently, Jones et al [15] experimentally demonstrated a significant reduction in the electric field dependence of low-ℓ Rydberg-Rydberg transition frequencies through the application of a non-resonant dressing field.…”
Section: Introductionmentioning
confidence: 99%
“…Spectroscopy of excited state transitions is of growing interest for a variety of applications including the search for stable frequency references [1,2], state lifetime measurement [3], optical filtering [4], frequency up-conversion [5], multiphoton laser cooling [6], as well as Rydberg gases [7,8] and their application to electro-optics [9][10][11] and nonlinear optics [12]. Twophoton excited state spectroscopy can be achieved without significant transfer of population out of the ground state using electromagnetically induced transparency (EIT) [13] in the ladder configuration [14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Rydberg EIT has been used to modify the frequency of light [11], study interactions in cold Rydberg gases [12,13,14] and probe electric fields inside vapour cells [15,16] and close to surfaces [17]. A feature of Rydberg states is the large dipole moment to nearby states which scales with the square of the principal quantum number, n 2 .…”
Section: Introductionmentioning
confidence: 99%